Greatly Enhanced Electrocatalytic N2 Reduction on TiO2 via V Doping. Issue 11 (17th June 2019) - Wu, Tongwei; Kong, Wenhan; Zhang, Ya; Xing, Zhe; Zhao, Jinxiu; Wang, Ting; Shi, Xifeng; Luo, Yonglan; Sun, Xuping
Abstract: As a sustainable alternative technology to the Haber–Bosch process, electrochemical N2 reduction offers the hope of directly converting N2 to NH3 at ambient conditions. However, its efficiency greatly depends on screening high‐active electrocatalysts for the N2 reduction reaction (NRR). Here, the recent experimental finding that V is an effective dopant to greatly improve the NRR performances of TiO2 toward ambient N2 ‐to‐NH3 fixation with excellent selectivity is reported. In 0.5 m anhydrous lithium perchlorate, V‐doped TiO2 nanorods attain a high Faradic efficiency of 15.3% and a large NH3 yield of 17.73 µg h −1 mgcat. −1 at −0.40 and −0.50 V versus reversible hydrogen electrode, respectively, rivaling the performances of most reported aqueous‐based NRR electrocatalysts. Density function theory (DFT) calculations are performed to gain further insight into the catalytic mechanism. Abstract : A V‐doped TiO2 nanorod efficiently electrocatalyzes the N2 reduction reaction with a Faradic efficiency of 15.3% and a NH3 yield of 17.73 µg h −1 mgcat. −1 at −0.40 and −0.50 V vs reversible hydrogen electrode, respectively, in 0.5 m LiClO4 . Density function theory calculations reveal such enhancement is attributed to synergistic effects of Ti and V.